Serum myoglobin after cardiac catheterisation. - McComb, J M (1982)
Study of 80 consecutive patients undergoing elective diagnostic cardiac catheterisation showed that after the procedure 25 (31%) developed myoglobinaemia. This was attributed to complications of the catheterisation in two. The remaining 23 had received premedication by intramuscular injection. In patients without intramuscular injections myoglobinaemia did not occur after uncomplicated cardiac catheterisation. The study did not support the proposition that cardiac catheterisation results in myocardial damage which can be detected by abnormalities of myoglobin but not by conventional indications of myocardial necrosis.